P-344 Number of cryopreserved embryos stored in Spain depending on their destination. (30th June 2022) - Nunez - Calonge, R; Nicolas, M; Abellan, F; Armijo, O; Baccino, G; Feito, L; Fuente, A. de la; Roca, M; Santalo, J
Abstract: Study question: How many frozen embryos are stored in Spain destined for donation to other couples, research, destruction, own use or abandoned? Summary answer: In Spain, 5% of frozen embryos are destined for donation to other patients, 17% are fated for research, 17, 7% for destruction and 12% are abandoned What is known already: According to the latest data from the Spanish Fertility Society (SEF) registry, the total number of embryos stored in Spain in 2019, was 668.082. Clinics ask patients to specify their preferences for the embryo's destinations such as: save the embryos for the future, donation to other patients, research, or discarding the embryos. Embryos were considered abandoned when a patient with frozen embryo/s stored failed to contact the clinic for > 2 years and the patient could not be located. However, it is not known how many embryos are assigned to each destination, neither in Spain nor in any other country Study design, size, duration: Reflecting concern about the accumulation of frozen embryos in banks, SEF convened a focus group with key figures in ethics, law, and reproductive medicine to identify possible solutions. The first step was to carry out a questionnaire to all the reproduction centres in Spain to know the number of frozen embryos stored and their destinations. A total of 242 IVF units were contacted through SEF newsletter and participants answered between April and July 2021 Participants/materials, setting, methods: Public and private IVF clinics which had cryopreserved embryos were sent questionnaires with requests regarding the number of frozen embryos in each destination: keeping for patients, donated to other patients who met donation criteria (same as for gamete donors) and who did not meet criteria, research to a specific project and without a project, destined for destruction that met the criteria established by law, and that did not meet criteria, and number of embryos abandoned. Main results and the role of chance: A total of 71 filled-in questionnaires from 242 IVF clinics were obtained. The response rate to the questionnaire was 29%. Of the respondents, a total of 376.445 stored embryos were reported. 46% of the total cryopreserved embryos were kept for later use by patients. 3.7% were donated to other couples but did not meet the criteria for donation: obtained from women over 35 years, or lack of any required test. 1.4% of the embryos were donated fulfilling the criteria for donation to other patients. 17% of the embryos were donated for research, but less than 1% had an assigned project. 17.7% of the frozen embryos were destined for termination of their conservation, and 1.4% of them did not meet the criteria established by law. A total of 46.046 embryos could be considered abandoned since the patients could not be contacted after more than two years of storage. This represents 12.2% of embryos without a defined destination. Limitations, reasons for caution: The main limitation of this study is the low response rate, since out of 242 centres, which obligatory sent their data to the National Registry in 2019, only 71 centres answered. This could be due to the lack of data from some reproduction units Wider implications of the findings: It is not known precisely how many frozen embryos have been abandoned in Spain, or what are their other destinations. Clinics are not required by authorities to report these number but to have concrete data on the frozen embryos is crucial to solve the problem of embryo accumulation in banks. Trial registration number: Not applicable